HOUSE OF BALLET : PRESENTING THE BEAUTY OF SPACE THROUGH DANCE CHOREOGRAPHY READINGS - Pradita, Raissa Anindya (Jurnal Poster Pirata Syandana, 2023)
Dance is an art form that deals with the movement of the body done rhythmically and is usually performed to music and within a given space. Due to the numerous benefits it offers, both physical and mental, dance has remained popular among people over time. In regard to that, well-designed dance facilities are needed to provide the optimum dance experience. Dance and architecture have long been considered to be two separate things, though both are closely related to human movement. Dance is an activity while architecture is often acknowledged as an object. As it develops, there has been a great deal of discussion about movement in architecture, one of which is the role of movement as a tool for spatial organization and arrangement. This paper tries to see the intriguing possibility of exploring dance and architecture at the same time, to see how the qualities found in dance movement, such as composition, feel, and dynamics, can be used as a basis for architectural programming to construct engaging spaces.